Does Volatility Spillover among Sectors Varies from Normal to Turbulent Periods? Evidence from Pakistan Stock Exchange - Abro, Asif Ali; Abubakar, Muhammad; Shahid, Tanveer Ahmad; Fatima, Urooj (Pakistan Journal of Humanities and Social Sciences, 2024)
This study investigates how six financial market performances are affected by spillover volatility sectors in both during and following the 2007 financial crisis in Pakistan. By offering a wealth of material to fill in the gaps during the 2007 pre- and post-financial crisis timeframe, this study adds to the body of current knowledge. The pre-crisis era, which ran from January 1, 2003, to December 31, 2007, was used for the analysis on the Pakistani sectors. The period from January 1, 2008, to December 31, 2015, was known as the post-crisis era. The Pakistan Stock Exchange and other sources provided the data, which was routinely gathered. An ARCH, GARCH & EGARCH model is used to investigate the asymmetric volatility spillover among the six industries. The results provide compelling evidence for the existence of a spillover impact in Pakistani businesses in the years after the crisis. Furthermore, there is a significant transmission of volatility throughout Pakistan's many industries during the financial crisis. Overall, the results provide insight into the varying degrees of integration between sectors in Pakistan, ranging from stable to volatile eras. The results indicate that no significant vulnerability was detected. Additional elements can be included and the timing of data can be adjusted. In this study, data is currently gathered monthly. However, in the future, data might be collected on a daily, weekly, or yearly basis to enhance the reliability of the data and its corresponding conclusions. This study expands the existing body of research on volatility and spillover effects in several industries of Pakistan. This research is an innovative study being conducted in six market sectors. The primary impetus for conducting this inquiry is the financial catastrophe in the United States, which has had repercussions on global markets as a whole. Moreover, this time frame is also utilized to inspect the correlation in between financial crises and stock market returns in Asian emerging markets.